Magnetic study of Fe3O4 nanoparticles incorporated within mesoporous silicon - VENKATESAN, MUNUSWAMY (Electrochemical Society, 2010)
Porous silicon PS matrices with oriented, separated pores grown perpendicular to the surface are used as a template for the incorporation of magnetite nanoparticles. The Fe3O4 particles used for infiltration into the PS template are coated with oleic acid in a hexane solution and exhibit an average diameter of 8 1.5 nm. The narrow size distribution and the superparamagnetic behavior at room temperature are interesting features of these nanoparticles. In addition, the use of PS as a template for the particle deposition influences and modifies the collective magnetic response of the nanoparticles. Especially, anisotropy between the two magnetization directions, magnetic field parallel and perpendicular to the surface, has been observed. Magnetite nanoparticles play a key role in medical applications, but also the magnetic properties of such a nanoparticle/PS system are of technical interest due to the transition between superparamagnetic and ferromagnetic behaviors. Temperature-dependent magnetization measurements are used to gain information about the magnetic interaction of the particles.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; ferromagnetic behaviors